Ethnological Background of the Sheep’ Names - Norkaitienė, Milda (Tautosakos darbai, 2017)
The subject of analysis comprises 287 Lithuanian sheep’ names. According to the author, traditionally the naming of sheep rests on somatic motivation (204 names, or 70.7 percent), including the animal’s color, its inborn or acquired bodily peculiarities or shortcomings, height, complexion, and age. Along with visible features, tactile appreciation of the wool’s quality and audible perception of the animal’s sounds are also important. 25 names (or 8.7 percent) of ethologically motivated zoonyms are related to denotative sphere, being influenced by the animal’s character, habits and manner. 53 (or 18.5 percent) names of evaluative and 5 names (1.7 percent) of subjective motivation reflect not only emotional, but also pragmatic relations between humans and animals. In order to emphasize belonging of the animal as a tangible property to a certain person, the sheep may acquire its owner’s name, surname or a metaphorical denomination of a specific mark that is exclusive to the owner and is tied onto the animal, or cut out on it, etc. Comparison of the motivation and metaphoric character of the names with broader linguistic, ethnological and folkloric context (including stable epithets, parallels, paremias, nicknames, zoomorphisms, the devil’s names and other mythical denominations, endearing names of the animals, customs of herding, relics of folk magic, etc.) shows that naming of animals is such a sphere, research of which enables experiencing vitality of the ancient beliefs, customs, and the mythical worldview. In terms of ethnology, the mythological contents of motivation for the name Rasa (‘dew’) seems particularly fascinating. The name has a magical function, as its etymon relates to the notion of water, thus naming of the sheep aims at ensuring and enhancing the quantity of its milk. In addition, this onomastic situation is far from accidental: a goat is known of having acquired a similar name (in diminutive, Raselė) for similar reasons. Besides, cows are also frequently given names deriving from appellatives or hydronyms related to water, e. g.: Banga (Lith. banga ‘wave’), Upė (Lith. upė ‘river’), or Agluona, Šešupė (Lithuanian hydronyms). Therefore, such phenomenon may be considered a systematic quality of the Lithuanian zoonyms.